Effectiveness of non-pharmacological interventions to manage anxiety in adolescents in the perioperative period: A systematic review and meta‑analysis - Pestana-Santos, Marcia; Pereira, Maria João; Pestana-Santos, Adriana; Santos, Eduardo; Goncalves, Andreia; Cardoso, Daniela; Lomba, Lurdes; Reis Santos, Margarida (Operating Room Nurses Association of Canada Journal, 2024)
Aims: To evaluate the effectiveness of non-pharmacological interventions to manage anxiety in adolescents in the perioperative period. Design: Systematic review of effectiveness and meta-analysis. Data sources: MEDLINE, CINAHL, PsycInfo, Cochrane Central Register of Controlled Trials, SciELO, sources of unpublished studies and grey literature, including Open Grey and RCAAP – Portugal, were systematically searched without time limits (up to December 2020). Review methods: This review followed the Joanna Briggs Institute (JBI) methodology for systematic reviews of evidence effectiveness. The selection process, critical analysis and extraction of data were performed by two independent reviewers. Studies were critically appraised using JBI Critical Appraisal Checklist for Randomised Controlled Trials. Data was synthesised through meta-analysis (using a fixedeffect model in the RevMan 5.2.8) and narrative synthesis. Results: This analysis included five studies with a total of 420 adolescents. The effectiveness of non- pharmacological interventions, including cognitive– behavioural techniques, hypnosis, guided imagery and relaxation, were examined in the perioperative context. A meta-analysis (n=136 adolescents) of three studies suggests no differences in adolescents’ anxiety when non-pharmacological interventions are applied compared to standard care (SMD -0.14, 95% CI - 0.48 to 0.20, p=0.42). Individually, all the studies showed that nonpharmacological interventions were beneficial on the reduction of the adolescents’ anxiety, although no statistical significance was found. Conclusion: Despite insufficient evidence on the effectiveness of non- pharmacological interventions, they should be considered as a resource in the management of adolescent anxiety in the perioperative period.